Book Forum on Hans Kundnani's Eurowhiteness: Culture, Empire and Race in the European Project - STEFAN AUER; PAVEL BARŠA; AGNES GAGYI; HANS KUNDNANI (Czech Journal of International Relations, 2024)
This book forum discusses Hans Kundnani’s pivotal book on “Eurowhiteness” and the role of race in the EU integration project. It includes three reactions from Stefan Auer, Pavel Barša, and Agnes Gagyi, along with Kundnani’s response. Eurowhiteness skillfully reveals what has been obscured by the European Union as a vehicle of “imperial amnesia”. The three reactions and the author’s response continue a polemical discussion on this imperial amnesia, as viewed through different intellectual traditions and regions, including Central and Eastern Europe and anti-colonial perspectives. As a result, the forum uses the book to either deepen the debate on the EU’s civilizationism with new perspectives or expand the Eurowhiteness narrative with new geo-historical contexts and connections. Issues of Russian imperialism in Ukraine, the Israeli war in Gaza, and the economic dimensions of European coloniality are brought to the foreground, particularly when viewed through the imagination and reality of Central (and Eastern) Europe.